THE HISTORY OF THE KAZAN TURKOLOGY SCHOOL: FOUNDATION AND THE ROLE OF ITS FOUNDERS - Khushmatova Dilsuz Abdullajonovna (Bright Mind Publishing, 2025)
This article examines the formation of the Kazan Turcology School in the 19th century, its development, and the scholarly legacy of its founders. It traces how Kazan University became a major center of Turkic and Oriental studies, with special emphasis on the Halfin dynasty and prominent scholars, analyzing their contributions in depth. The study also explores the school’s impact in both the Russian Empire and the broader Turkic-speaking world.
Keywords: Kazan Turcology School, Kazan University, Turcology, Halfin dynasty, Ibrahim Halfin, Kristian Danilovich Fran, Fyodor Erdman, Oriental studies, Tatar language, scholarly legacy.